Measurement of the mass difference and relative production rate of the Ω−b and Ξ−b baryons - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kubat, Jakub; Leverington, Blake; Marks, Jörg; et al. (Physical review, 2023)
The mass difference between the Ω−b and Ξ−b baryons is measured using proton-proton collision data collected by the LHCb experiment, corresponding to an integrated luminosity of 9 fb−1, and is found to be m(Ω−b)−m(Ξ−b)=248.54±0.51(stat)±0.38(syst) MeV/c2. The mass of the Ω−b baryon is measured to be m(Ω−b)=6045.9±0.5(stat)±0.6(syst) MeV/c2. This is the most precise determination of the Ω−b mass to date. In addition, the production rate of Ω−b baryons relative to that of Ξ−b baryons is measured for the first time in pp collisions, using an LHCb dataset collected at a center-of-mass energy of 13 TeV and corresponding to an integrated luminosity of 6 fb−1. Reconstructing beauty baryons in the kinematic region 2<η<6 and pT<20 GeV/c with their decays to a J/ψ meson and a hyperon, the ratio fΩ−bfΞ−b×B(Ω−b→J/ψΩ−)B(Ξ−b→J/ψΞ−)=0.120±0.008(stat)±0.008(syst), is obtained, where fΩ−b and fΞ−b are the fragmentation fractions of b quarks into Ω−b and Ξ−b baryons, respectively, and B represents the branching fractions of their respective decays.